2022
DOI: 10.3390/molecules27175584
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Technological Advancements in the Possible Food Applications of Spirulina and Their Health Benefits: A Review

Abstract: Spirulina is a kind of blue-green algae (BGA) that is multicellular, filamentous, and prokaryotic. It is also known as a cyanobacterium. It is classified within the phylum known as blue-green algae. Despite the fact that it includes a high concentration of nutrients, such as proteins, vitamins, minerals, and fatty acids—in particular, the necessary omega-3 fatty acids and omega-6 fatty acids—the percentage of total fat and cholesterol that can be found in these algae is substantially lower when compared to oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 137 publications
(228 reference statements)
0
44
1
Order By: Relevance
“…The pharmacological properties of Spirulina, that is, its anticarcinogenic, antiviral, antimicrobial, anti-inflammatory and antitumoral activities, have been directly related to the presence of phenolic compounds [ 9 , 12 ]. Figure 3 shows the total phenolic content (TPC) after each test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacological properties of Spirulina, that is, its anticarcinogenic, antiviral, antimicrobial, anti-inflammatory and antitumoral activities, have been directly related to the presence of phenolic compounds [ 9 , 12 ]. Figure 3 shows the total phenolic content (TPC) after each test.…”
Section: Resultsmentioning
confidence: 99%
“…Its pigments include beta-carotene, chlorophyl and phycocyanin, the last of which is an antioxidant and anti-inflammatory compound used in the cosmetic and pigment industries. In addition, some studies have indicated that a series of phenolics compounds can be found in this microalga as caffeic, chlorogenic, salicylic, synaptic and trans-cinnamic acids, which act individually or synergistically with other antifungal and antioxidant compounds [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lipid concentration of Arthrospira platensis can vary from ca. 5 to 10% (of the dry weight) [ 60 ]. Long-chain FA are predominant compounds in Spirulina (mainly palmitic acid and gamma-linoleic acid) [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Omega-6 constitutes the majority of the total Spirulina FA [ 66 , 67 ]. Furthermore, Spirulina contains a significant amount of palmitic acid (16:0), which represents more than 25% from the total fat content [ 60 ]. PUFA levels in Spirulina ranged from 1.5 to 2.0% of total fat [ 68 ], whereas PUFA content represented 30% of the total fat content [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…They are widely used by researchers to develop meat substitutes [ 48 , 49 ]. Currently, nutritionists confirm that Spirulina is an excellent source of natural protein food, and it contains up to 60–70% protein content, where human absorption rate are up to 95% [ 50 , 51 ]. This is great news for vegetarians and researchers developing alternative plant proteins.…”
Section: Classification Of Algal Food and Its Application In Food Ind...mentioning
confidence: 99%